Evaluating Life Expectancy Evaluations. Issue 2 (3rd April 2018) - Bauer, Daniel; Fasano, Michael V.; Russ, Jochen; Zhu, Nan
Abstract : The quality of life expectancy estimates is one key consideration for an investor in life settlements. The predominant metric for assessing this quality is the so-called A-to-E ratio, which relies on a comparison of the actual to the predicted number of deaths. In this article, we explain key issues with this metric: In the short run, it is subject to estimation uncertainty for small and moderately sized portfolios; and, more critically, in the long run, it converges to 100% even if the underwriting is systematically biased. As an alternative, we propose and discuss a set of new metrics based on the difference in (temporary) life expectancies . We examine the underwriting quality of a leading U.S. life expectancy provider based on this new methodology.